2008
DOI: 10.21161/mjm.12208
|View full text |Cite
|
Sign up to set email alerts
|

Changes of raffinose and stachyose in soy milk fermentation by lactic acid bacteria from local fermented foods of Indonesian

Abstract: The objective of this study was to evaluate the fermentative characteristics of lactic acid bacteria isolated from local fermented foods and consume raffinose and stachyose during fermentation soymilk. Lactobacillus plantarum pentosus SMN, 01, Lactobacillus casei subsp rhamnosus FNCC, 098, Lactobacillus casei subsp rhamnosus FNCC, 099, Streptococcus thermofilus, 001, Lactobacillus delbrueckii subsp. bulgaricus FNCC, 0045, Lactobacillus plantarum SMN, 25, and Lactobacillus plantarum pentosus FNCC, 235 exhibited… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 15 publications
2
6
0
Order By: Relevance
“…Thus the loss of viability during storage increased with using soy milk in Labneh production. The obtained results agreed with Sumarna [27]. Slight increases were found in the viable counts of L. acidophilus in soy milk Labneh.…”
Section: Microbial Analysis Of Labnehsupporting
confidence: 88%
“…Thus the loss of viability during storage increased with using soy milk in Labneh production. The obtained results agreed with Sumarna [27]. Slight increases were found in the viable counts of L. acidophilus in soy milk Labneh.…”
Section: Microbial Analysis Of Labnehsupporting
confidence: 88%
“…bulgaricus grew poorly in soymilk because of their inability to ferment sucrose and other carbohydrates in soymilk. Sumarna, (2008) reported that S. thermofilus, 001 grew better than L. casei subsp rhamnosus FNCC, 098 L. casei subsp rhamnosus FNCC, 099, and L. delbrueckii subsp. bulgaricus FNCC, 0045 and produced higher organic acid than the latter during fermentation of soy milk.…”
Section: Microbial Examination Of Yoghurtmentioning
confidence: 99%
“…calibration curve. The concentration of oligosaccharides was determined based on a standard curve and expressed in milligrams of sugar per 100 ml of soy milk [27].…”
Section: The Examined Materials Used In the Study And The Methodology Of The Experimentsmentioning
confidence: 99%